EFFECTIVENESS OF TREATMENT METHODS FOR ACUTE CHOLECYSTITIS COMPLICATED BY CHOLEDOCHOLITHIASIS - Safoev Bahodir Barnoevich; Radjabov Anvar Islamovich; Yarikulov Shukhrat Shakirovich (Western European Studies, 2024)
The methods of choledocholithiasis treatment, which are currently used in clinics of the Russian Federation, has been presented. The problems of diagnosis and treatment of gallstones (GSD) in individuals of different age groups are spotlighted. In the study of treatment of cholelithiasis and choledocholithiasis, including arising complications, it can be concluded that so far the ideal method of treatment of this pathology has not been found. Up to now, the majority of doctor’s main treatment is surgical removal of gall stones by some method or other
Keywords: cholelithiasis; choledocholithiasis; conservative treatment; surgical treatment